Sports vocabulary: political and everyday discourse - Sedykh, Arkadiy Petrovich; Akimova, Elvira Nikolajevna; Skvortsov, Konstantinviktorovich; Shcherbakov, Andrey Vladimirovich; Zhukova, Arina Gennadievna (Universidade Estadual Paulista, Faculdade de Ciências e Letras de Araraquara, 2021)
The problems of the functioning of sports vocabulary in the semiotic space of political and everyday discourse in France are considered in the study. The characteristics of the components of the discourse picture of the world of the French linguoculture are described, the key element of which is the linguistic personality of the politician and the generalized native speaker. The analysis of factual data is based on a linguistic semiotic approach to their interpretation, as a rule, within the framework of a discourse statement, as well as at the level of the nominative fund of the national language. Sports terminology is considered at the level of general linguistic and ethnocultural dominants of the national discourse. The allocation of the national-cultural component of the lexeme of a sports theme allows studying sportonyms from the point of view of finding information about French linguistic culture, discourse, and linguistic thinking in their usus.